Ashes and Donation: Jacques Derrida’s Gray Phenomenology - Mistral, Ramón (Escritura e Imagen, 2023)
This article seeks to reconstruct Derrida’s position regarding the phenomenological problem of givenness. Using Jean-Luc Marion’s description of saturated phenomena as a reference point, I argue that Derrida questions the possibility of an excess of intuition. I propose an interpretation of key moments in his thought to demonstrate that the generalization of writing implicitly attributes impure donation to all phenomena. In other words, a donation from which absolute certainty cannot be derived and which necessitates rejecting the supposed singularity of any phenomenon, including aesthetic ones that serve as a paradigm for the saturation trope.